European guidance for the diagnosis and management of osteoporosis in postmenopausal women. - Kanis, J; Burlet, N; Cooper, C; Delmas, P; Reginster, J; Borgstrom, F; Rizzoli, R (2008)
UNLABELLED: Guidance is provided in a European setting on the assessment and treatment of postmenopausal women with or at risk from osteoporosis. INTRODUCTION: The European Foundation for Osteoporosis and Bone disease (subsequently the International Osteoporosis Foundation) published guidelines for the diagnosis and management of osteoporosis in 1997. This manuscript updates these in a European setting. METHODS: The following areas are reviewed: the role of bone mineral density measurement for the diagnosis of osteoporosis and assessment of fracture risk; general and pharmacological management of osteoporosis; monitoring of treatment; assessment of fracture risk; case finding strategies; investigation of patients; health economics of treatment. RESULTS AND CONCLUSIONS: A platform is provided on which specific guidelines can be developed for national use.